2002
DOI: 10.1177/153537020222700308
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Fails to Modulate Immune Parameters Influenced by Calorie Restriction in Aging Fischer 344 Rats

Abstract: The aim of this study was to determine if long-term treatment with melatonin (MEL), a purported anti-aging agent, was as effective as calorie restriction (CR) in modulating immune parameters in aging Fischer 344 male rats. Splenic lymphocytes were isolated from 17-month-old rats that, beginning at 6 weeks of age, were treated with MEL (4 or 16 μg/ml in drinking water) and from 17-month-old rats fed ad libitum (AL) or rats fed a CR diet (55% of AL intake). The number of splenic T cell populations and T cell sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…1986; Pahlavani 2000; Ha et al . 2001; Pahlavani et al 2002), including the proliferative capacity and functioning of T‐ and B‐cells (Nakamura et al . 1990; Kubo et al .…”
Section: Discussionmentioning
confidence: 99%
“…1986; Pahlavani 2000; Ha et al . 2001; Pahlavani et al 2002), including the proliferative capacity and functioning of T‐ and B‐cells (Nakamura et al . 1990; Kubo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in Fischer 344 rats showed that 40% DR attenuated the age-related decline in pineal function and melatonin secretion [24]. However, the immune response in rats following melatonin supplementation was not improved as it was with DR [25].…”
Section: Melatoninmentioning
confidence: 99%
“…Some reports indicate that CR reduces endogenous NK cell activity in the spleen of mice and impairs enhancement of NK cell activity in the lung after intranasal infection of the influenza virus, 21,22) but another study clarified that CR did not affect endogenous NK cell activity and enhanced IL-2-induced NK cell activity in rats. 23) We have observed that the cytolytic activity of NK cells declined in younger mice (11 weeks old) but not in older mice (22 weeks old) even when they were similarly subjected to 40% DR. These results indicate that the influence of DR on NK cells varies depending on age-related changes in immune functions.…”
Section: Discussionmentioning
confidence: 82%